1995
DOI: 10.1177/073168449501401102
|View full text |Cite
|
Sign up to set email alerts
|

Low Velocity Impact Fatigue Studies on Glass Epoxy Composite Laminates with Varied Material and Test Parameters-Effect of Incident Energy and Fibre Volume Fraction

Abstract: An effort was made to study the effects of fibre volume fraction and incident energy on the impact damage tolerance of composite laminates subjected to low velocity impacts at constant strike velocities. Repeated drop tests were conducted using an in-house built drop weight impact tester. Delamination area was used as a parameter for quantifying damage while the number of drops (impacts) to failure used to assess the damage tolerance limits. The delamination area was found to increase and then saturate after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 10 publications
0
16
0
3
Order By: Relevance
“…Ray et al [8], working with a jute/vinyl-ester composite in a cyclic Charpy test, saw increases in the endurance of the material as the impact energy decreased. Some researchers [9,10] have also identified a threshold energy, below which no visible delamination is seen. Yuan et al…”
Section: Introductionmentioning
confidence: 99%
“…Ray et al [8], working with a jute/vinyl-ester composite in a cyclic Charpy test, saw increases in the endurance of the material as the impact energy decreased. Some researchers [9,10] have also identified a threshold energy, below which no visible delamination is seen. Yuan et al…”
Section: Introductionmentioning
confidence: 99%
“…In Ray et al (2002), a jute/vinyl-ester composite in a cyclic Charpy test showed an increase in the material's endurance as the impact energy decreased. Such graphs are divided by some researchers into several regions (Roy et al, 2001), and in some cases, it was possible to identify a threshold energy, below which no visible delamination was observed (Khan et al, 1995;Sınmazçelik et al, 2006). However, it was mentioned in Harris (2000) that in FRPCs, low-energy transversal impacts, which were insufficient to leave any visible damage under the surface, could produce internal damage capable to grow under the influence of subsequent cyclic loading.…”
Section: Frpc Under Impact and Fatiguementioning
confidence: 98%
“…However, a more common way to analyse the fatigue life reduction during IF was to use the curves presenting a link between the level of energy and the number of cycles to failure (EÀN F ) plotted in most cases in semi-logarithmic coordinates (Jang et al, 1992;Khan, Rao, & Venkataraman, 1995;Ming-Hsiung, Hwang, Doong, & Fung, 1999;Ray, Sarkar, & Bose, 2002;Roy, Sarkar, Rana, & Bose, 2001;Sınmazçelik et al, 2006). In Ray et al (2002), a jute/vinyl-ester composite in a cyclic Charpy test showed an increase in the material's endurance as the impact energy decreased.…”
Section: Frpc Under Impact and Fatiguementioning
confidence: 99%
“…Além disso, há de se considerar a possibilidade da repetição destes choques mecânicos de baixa energia, configurando a chamada fadiga por impacto, que ocorre tipicamente em algumas posições específicas de uma aeronave (e.g., bordos de ataque, fuselagem, soalhos, revestimentos internos). Num contexto propício, estes múltiplos impactos podem culminar em danos de grande monta e na substancial degradação das propriedades mecânicas do material [13][14][15].…”
Section: Danos Por Impactounclassified